Psychological Distress of High School Graduates During Social Distancing in Croatia - Ćurković, Natalija; Bugarin, Jelena; Lukacin, Lorelaj (European Journal of Mental Health, 2022)
Introduction: The COVID-19 pandemic has influenced the whole world, thus also affecting the high school graduates in Croatia. Aims: The purpose of the study was to examine the psychological distress high school graduates experienced during the COVID-19 social distancing measures, more precisely to investigate gender and school type differences and to examine the relationship between psychological distress and self-regulated learning. Methods: In this cross-sectional study, an online questionnaire was administered to 13,037 high school graduates across Croatia. Results: The results show that girls exhibit higher levels of psychological distress compared to the boys, while the art school graduates show the highest distress, followed by gymnasium (i.e., secondary grammar school, prep school) graduates, and lastly vocational school graduates. Furthermore, a moderate negative correlation was found between self-efficacy and psychological distress, and significant, but small correlations were found between regulation of effort, management of work, time and environment, self-handicapping as well as elaboration and psychological distress. These results show that higher levels of self-regulation are connected to lower levels of psychological distress. Conclusions: These findings demonstrate that a need exists for greater accessibility of mental health care for adolescents.